1976
DOI: 10.1007/bf00496860
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of acute and chronic behavioural effects of methamphetamine in the mouse

Abstract: A simple and reliable method was developed for rating the dose-related behavioural effects of methamphetamine in male Swiss Albino mice for acute or chronic drug treatment. This procedure was based on a frequency count of certain behaviours made at 15-min intervals over a 90-min period following drug administration. The Fisher Randomization procedure was adapted to analyze behavioural data for the chronic studies. Clear-cut, dose-related behavioural responses occurred following acute (+)-methamphetamine admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…Amphetamine pro duced two types of behavioral effects in rats that may be related to brain catecholamines: enhanced locomotor activity and stereotyped behavior. Similar dose-related behavioral effects by methamphetamine have been observed in mice (1). It is now generally assumed that the behavioral effects of amphetamine resulted from the ability of these drugs to release catecholamines from nerve terminals in the central nervous system (2)(3)(4)(5).…”
mentioning
confidence: 66%
“…Amphetamine pro duced two types of behavioral effects in rats that may be related to brain catecholamines: enhanced locomotor activity and stereotyped behavior. Similar dose-related behavioral effects by methamphetamine have been observed in mice (1). It is now generally assumed that the behavioral effects of amphetamine resulted from the ability of these drugs to release catecholamines from nerve terminals in the central nervous system (2)(3)(4)(5).…”
mentioning
confidence: 66%
“…The central action of MAP is mediated through noradrenergic, dopaminergic and serotonergic neurons (24). It has been known that repeated exposure to psychostimulants produces behavioral sensitization and an exaggerated motor response to subsequent challenge administration of psychostimulants (17,18,25). Efforts to elucidate the neurochemical mechanisms involved in the development of behavioral sensitization to psychostimulants have found that this phenomenon is at least partly due to increasing basal extracellular levels of DA in the mesolimbic terminal areas when the animals are receiving daily psychostimulants injections (19 -21).…”
Section: Discussionmentioning
confidence: 99%
“…Repeated administration of methamphetamine (MAP) can cause functional supersensitivity (17,18). This phenomenon is at least partly due to the increasing basal extra-cellular levels of DA in the mesolimbic terminal areas when the animals are receiving daily psycho-stimulant injections (19 -21).…”
mentioning
confidence: 99%
“…Behavioral effects and dopaminergic mechanisms of amphetamines in the mouse have been demonstrated to be similar to those in the rat (3,4 and stereotyped behavior (gnawing, licking or sniffing). Ten ratings were made over a 90-sec period at exactly 10-sec intervals.…”
Section: Repeated Administrationmentioning
confidence: 90%